3D Printing-A "Touch-Button" Approach to Manufacture Microneedles for Transdermal Drug Delivery - Merima Sirbubalo; Amina Tucak; Kenan Muhamedagic; Lamija Hindija; Ognjenka Rahić; Jasmina Hadžiabdić; Ahmet Cekic; Derzija Begic-Hajdarevic; Maida Cohodar Husic; Almir Dervišević; Edina Vranić (MDPI AG, 2021)
Microneedles (MNs) represent the concept of attractive, minimally invasive puncture devices of micron-sized dimensions that penetrate the skin painlessly and thus facilitate the transdermal administration of a wide range of active substances. MNs have been manufactured by a variety of production technologies, from a range of materials, but most of these manufacturing methods are time-consuming and expensive for screening new designs and making any modifications. Additive manufacturing (AM) has become one of the most revolutionary tools in the pharmaceutical field, with its unique ability to manufacture personalized dosage forms and patient-specific medical devices such as MNs. This review aims to summarize various 3D printing technologies that can produce MNs from digital models in a single step, including a survey on their benefits and drawbacks. In addition, this paper highlights current research in the field of 3D printed MN-assisted transdermal drug delivery systems and analyzes parameters affecting the mechanical properties of 3D printed MNs. The current regulatory framework associated with 3D printed MNs as well as different methods for the analysis and evaluation of 3D printed MN properties are outlined.